Designing and implementing Web API for RAI software - Xue, Siyuan (2019)
The information silo becomes a significant problem with the software evolution from desktop applications to web-based applications. In this thesis, the research problem is derived from a customer's requirement to integrate two different health information systems. The design and creation research approach is employed in this study, which involves aware, suggestion, development, evaluation and conclusion. This paper focuses on building Web Service to break the information silo in healthcare systems, especially between the Electronic Health Record (EHR) and other health information systems. As the outcome of this study, a RESTful Web API is constructed to resolve the information silo issue. Meanwhile, the different alternative solutions to construct each component of the Web API and open issues are summarized in the evaluation phase.